What is the Theology of Women's Ministry? - Edwards, Ruth B. (Scottish journal of theology, 1987)
The theology of women's ministry is a comparatively new item on the Church's agenda. It is less than two decades since the Church of Scotland took the historic decision to open its ordained ministry to women. At the time it seemed a controversial step, and many must have wondered where it would lead the Kirk. I think that we can truthfully say that it has not led to any dire disasters, but rather to the enrichment of the ministry. That has also been the experience of many other Churches which in recent years have opened their ordained ministry to women. But controversies remain. The 1985 General Synod elections in the Church of England were dominated by the issue of women's ordination, with feelings running high in pressure-groups on both sides. In some Churches the introduction of women's ordination has exacerbated divisions already existing among members. Some of the major Christian denominations, including both the Roman Catholic and Eastern Orthodox churches, do not permit any form of ordination for women. Even within denominations like the Church of Scotland, where the introduction of women ministers has occurred without disruption, there are still members who have doubts about whether it is really right. In many small Christian groups women are debarred from all but the most informal ministry, because it is considered unbiblical for them to preach, address assembled Christians publicly, or presume to teach men about spiritual matters.